RETHINKING THE PLACE OF RELIGIOUS DISCOURSE IN ACADEMIC DISCOURSE: A CRITIQUE OF AMBER ENGELSON - Setiono Sugiharto (Universitas Katolik Indonesia Atma Jaya, 2013)
This article critiques some arguments on religious discourse in thecontext of academic discourse recently proposed by Engelson(2014). In relation to this critique, four points are raised: religiousidentities in academic discourse, structural inequities of the spreadof English in the Indonesian context, Indonesian rhetoricaltraditions, and the role of religious expression in academicdiscourse.Keywords: religious discourse, academic discourse, religiousidentities, Indonesian rhetorical traditions, religiousexpression.